Computational triangulation in the digital age of mathematics teacher education: an example - Abramovich, Sergei (Computer Tools in Education, 2025)
What is triangulation? Whereas the very idea of triangulation can be traced back to the 6th century B.C. as a method of indirect measurements of distances and heights [1], nowadays, different subject matters use this term when scholarly attempts to make research rigorous can be described as a construction of a triangle. Most notably, triangulation has been used by sociologists as a way of taking a look at a certain experimental outcome from at least two different perspectives, by connecting three points – the outcome as the focus of research and two alternative perspectives – thus forming a triangle. When there are more than two alternative perspectives, more than one triangle can be constructed. These ideas stem from the works of sociologists [2-6]. In the cited works, different types of triangulation have been considered including methodological triangulation [2], theoretical triangulation [5], “triangulation between methods and triangulation within a method” [6, p. 217, italics in the original], and triangulation by data sources [5].